Guided tissue regeneration/deproteinized bovine bone mineral or papilla preservation flaps alone for treatment of intrabony defects. II: radiographic predictors and outcomes - Antonio LinËœ ares (journal of clinical periodontology, 2006)
Objectives: This study reports the secondary analysis of a randomized-controlled clinical trial designed to assess the efficacy of deproteinized bovine mineral and a collagen membrane in the treatment of intrabony defects. The specific aims of this report are (1) to analyse the radiographic bone changes 1 year after therapy and (2) to assess the association between radiographic defect angle and treatment outcomes. Materials and Methods: Baseline and 12-month radiographs were collected from 120 patients with advanced chronic periodontitis from 10 centres in seven countries as part of a multi-centre clinical trial. All patients had at least one intrabony defect X3mm in depth. The treatment consisted of simplified or modified papilla preservation flaps to access the defect. After debridement of the area, a deproteinized bovine mineral and a collagen membrane were applied in the test subjects, and omitted in the controls. Main outcome measures were radiographic bone fill and defect resolution 1 year after surgery. Results: One hundred and twenty pairs of radiographs were obtained, of which 110 pairs were measurable (57 tests and 53 controls). One year after treatment, radiographic resolution of the intrabony component was significantly higher in the test group (3.2 1.7mm) when compared with the controls (1.7 1.9mm). Multivariate analysis indicated that the treatment and the baseline radiographic depth of the intrabony defect significantly influenced the radiographic bone fill of the intrabony defect 1 year following treatment. The percentage of resolution of the defect was influenced by the treatment provided and the baseline plaque score. The baseline radiographic defect angle did not show a significant impact on the clinical and radiographic outcomes. Conclusions: Regenerative periodontal surgery with a deproteinized bovine bone mineral and a collagen membrane offered additional benefits in terms of radiographic resolution of the intrabony defect and predictability of outcomes with respect to papilla preservation flaps alone.